Sorghum grain yield and nutrient dynamics under varying rates of fertilizer application in the Sub-Sudanian Zone of Burkina Faso - Dieudonné, Ouattara (2016)
A thesis presented to the Department of Crop and Soil Sciences, Faculty of Agriculture, College of Agriculture and Natural Resources, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana, in partial fulfillment of the requirements for the award of the Degree of Master of Philosophy in Soil Science, 2015